Antecedents And Outcomes Of Export Pricing Practices Evidence From Global Production Hub In Penang - Ata Mohammad, Al Tawalbeh Mahmoud (2020)
The Penang export hub is a unique example of a government policy due to its development priorities with emerging opportunities for international specialization initiated by the ongoing process of global production sharing. This study aims to investigate the antecedents and outcomes of export pricing practices. It also intends to examine the relationship of international experience, technological turbulence, psychic distance, export pricing practices and export performance (export intensity (EI), export growth (EG), export profitability (EP)) amongst MNEs at the global production hub in Penang. The moderating effects of competitive intensity in the relationship between export pricing practices (EPP) and export performance (EP) (EG, EI, EP) are also examined. To test the framework, Resource-based View (RBV), Contingency Theory (CT) and Organizational Learning Theory (OLT) were employed in this study.